Analisis Meningkatnya Kenaikan Temperatur Air Pendingin Pada Mesin Induk Jhoni XLV - Rahmadana Rijal, Rahmadana; Florentina Florentina; Rusman Rusman (KALAO'S MARITIME JOURNAL, 2022)
The background of this research is the incident that occurred on board the ship which experienced problems with the cooling system on the Jhoni XLV main engine on July 9 2022 at 05.30 LT (Local Time) when the ship was sailing from Batulicin to Batam, the cooling water temperature increased to 78° C. The method used in this study is a qualitative method that produces descriptive data in the form of written words from people and observed behavior. The data source used is primary data obtained directly from the research site by making observations related to the title of Applied Scientific Work. The results of the research and discussion of the problems in this Applied Scientific Work show that the implementation of Maintenance at Jhoni XLV must be further improved. Due to the lack of implementation of maintenance on board.